'Removed from humanity': a qualitative analysis of attitudes toward abortion providers in anti-abortion individuals in Canada. (8th August 2018) - Duerksen, Kari N.; Lawson, Karen L.
Abstract: Objective: The present study explores the content of abortion provider stigma. Background: Abortion stigma extends beyond women who have abortions to abortion providers. Previous analyses of anti-abortion bills and rhetoric have revealed stereotypes of abortion providers as dangerous and less trustworthy than other health professionals. Methods: We present a thematic analysis of one-on-one interviews about attitudes toward abortion providers with Canadian individuals ( N = 21) holding an anti-abortion stance. Results: We found participants held two kinds of beliefs about abortion providers: (1) providers are agentic and intentional actors and (2) providers are non-agentic victims of a larger system. While the former subtype of provider was viewed with hostility and disgust, the latter was viewed with pity, with participants suggesting that restriction of abortion would be beneficial for provider well-being. Conclusion: We document a new component of abortion provider stigma: the belief that abortion providers are harmed by abortion and that they are to be pitied for this. This 'abortion harms providers' attitude parallels recent anti-abortion arguments that abortion harms women. These stigmatising attitudes both construct the provider as untrustworthy and unable to properly care for women.